Digital Device Usage Patterns, Social-Emotional Functioning, and Elementary Students’ Learning Outcomes: Evidence from Indonesia - Andina Lucky Puspa Dini; Kukuh Andri Aka (The Indonesian Institute of Science and Technology Research, 2026)
Digital devices have become an integral part of primary school students' daily lives, while social-emotional functioning is increasingly recognized as an important factor in academic development. This study aimed to examine the relationship between digital device use patterns, social-emotional functioning, and academic achievement among fifth-grade primary school students. The study employed a quantitative cross-sectional correlational design involving 29 students selected through total sampling. Data were collected using two closed-ended Likert-scale questionnaires and students' summative academic scores. The digital device use questionnaire retained 17 valid items, while the social-emotional questionnaire retained 14 valid items. The data were analyzed using descriptive statistics, validity and reliability testing, Shapiro–Wilk normality, linearity testing, and simple as well as multiple regression analyses. The findings showed that digital device use patterns were significantly associated with academic achievement in the simple model (p = 0.036), and social-emotional functioning was also significantly associated with academic achievement (p = 0.018). However, when both predictors were tested simultaneously, the model did not reach statistical significance (p = 0.056). These findings indicate that digital device use and social-emotional functioning are each related to students' learning outcomes, although their combined contribution was not confirmed in the present model. The study highlights the importance of understanding digital device use contextually and strengthening students' social-emotional functioning to support learning in primary education.